Motivasi dan Aktivitas Wisata pada Perhelatan/Event Sleman Temple Run - Novitasari, Dian (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
The Sleman Tourism Office has unveiled Sleman Regency as a sports tourism destination, with one of its offerings being the Sleman Temple Run (STR). The aim of STR is to showcase the potential of Sleman Regency and bolster tourism activities. This study seeks to understand the motivation and behavior of sports tourists participating in the Sleman Temple Run event in 2022. The research methodology involves descriptive quantitative analysis, utilizing both primary and secondary data gathered through questionnaire distribution and literature review. The analysis process includes data examination, grouping, tabulation, and analysis. The findings present participant profiles, an analysis of the motivations of STR 2022 participants, both in general and specific to sports tourism, and the tourism activities they engaged in. Firstly, tourist profiles are delineated based on geographical and demographic aspects. Secondly, the highest general motivation among participants is physiological, while specific motivation related to sports tourism is physical fitness. Thirdly, participant activities predominantly involve trail running, with 62.07% opting for this activity, while 37.93% engage in other activities. From these findings, it can be inferred that while the Sleman Temple Run contributes to increased tourist visitation in Yogyakarta City, particularly in Sleman Regency, the impact may not be significant.